Implementation of Automatic Feeding and Monitoring of Pet Development Based on Telecommunication Networks and Android - Valioenza, Difa (Faculty of Engineering, Universitas Tanjungpura, 2026)
Increasingly busy daily activities make it difficult for pet owners to feed their pets on time and monitor their development. This can cause discomfort for owners and potential health problems for pets. How can feeding be automated and anabul (fur babies) development be monitored so that pet owners can more easily and efficiently care for their pets amidst their busy schedules? This study aims to design and develop an automatic feeding device and anabul development monitoring system based on telecommunication networks and Android. The designed device is capable of monitoring anabul development by periodically measuring their weight. Data obtained over a week show that the anabul's weight increased well from Monday to Sunday. Additionally, the device's food level reading functions well over the course of a week, ensuring that feeding occurs according to the set schedule.